Pengelolaan Media Sosial Instagram Sebagai Media Publikasi Direktorat Sekolah Menengah Atas Fatmawati - Atandy Shella Puspita Sari; Shinta Kristanty (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study discusses the management of Instagram @direktorat.sma as a media publication of the Direktorat of SMA Fatmawati under the auspices of Kemendikdasmen. Although Instagram @direktorat.sma is used for publication, its management still faces limitations in following the latest trends. This study aims to analyze the management of social media based on the concept of 4C Chris Heuer (Context, Communication, Collaboration, Connection) with a descriptive qualitative approach. The research data included primary data through participatory observation, structured interviews, and documentation, as well as secondary data from scientific articles, Instagram uploads, and related publication materials. The results show that @direktorat.sma has implemented social media management with context management through routine content planning or content plans and visual guidelines, as well as using KBBI rules. Communication management is achieved through two-way communication, such as quizzes, live streams, competitions, and responding to comments and direct messages. Collaboration is carried out with High School Ambassadors to present creative and educational content, while other Directorate units focus on delivering priority programs. Connection management is realized by showcasing student achievements and High School Ambassador activities, thereby building closeness and engagement with the audience.